2018
DOI: 10.1007/s40273-018-0652-3
|View full text |Cite
|
Sign up to set email alerts
|

Does Non-Adherence Increase Treatment Costs in Schizophrenia?

Abstract: Inference from analysis of administrative data is limited by the risk of selection bias. Inference from trials is limited by small sample sizes. The literature does not consistently support an assumption that non-adherence increases healthcare costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
(160 reference statements)
0
9
0
2
Order By: Relevance
“…Although an increase in hospitalization costs is typically observed with AP non-adherence, this increase is often offset by decreased pharmacy costs. 12 The current study found that non-adherent patients with uncontrolled symptoms of schizophrenia incurred $20,787 higher mean healthcare costs annually compared to patients without schizophrenia. This cost difference appears to be higher than the cost difference between all patients with and without schizophrenia ($14,087).…”
Section: Baseline Characteristicsmentioning
confidence: 58%
See 2 more Smart Citations
“…Although an increase in hospitalization costs is typically observed with AP non-adherence, this increase is often offset by decreased pharmacy costs. 12 The current study found that non-adherent patients with uncontrolled symptoms of schizophrenia incurred $20,787 higher mean healthcare costs annually compared to patients without schizophrenia. This cost difference appears to be higher than the cost difference between all patients with and without schizophrenia ($14,087).…”
Section: Baseline Characteristicsmentioning
confidence: 58%
“…patients with schizophrenia who are not adherent to AP therapy are commonly reported. 12,20 Of note, patients older than 65 years comprised a lower share (12%) of non-adherent patients with uncontrolled symptoms of schizophrenia, which may explain the lower contribution of LTC visits to the mean total healthcare cost difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, associations between adherence and costs should be interpreted with caution because prior studies have reported adherence is associated with higher pharmacy costs but not overall cost savings 29 . Although findings in the literature are mixed, the current study has found evidence of decreased total medical and total costs in spite of an increase in pharmacy costs.…”
Section: Discussionmentioning
confidence: 98%
“…Research on registry data is rare. Most of the available studies analyze one aspect of healthcare for patients with schizophrenia, for instance the use of antipsychotic medication, costs, family services, or continuity of care[5,8,10,2325,5054]. Our examination of the relationship between continuity of care, co-payments and episodic psychiatric care, with acute psychiatric care as a proxy of quality of care, is new and encompasses all types of care available.…”
Section: Conclusion and Discussionmentioning
confidence: 99%